Peran Pondok Pesantern Modern Uwais AL-Qarni dalam Penerapan Nilai-Nilai Islam Moderat - Lega Lesmana (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
Uwais Al-Qarni Modern Islamic Boarding School is a boarding school located in Tempilang Village, Tempilang District, West Bangka Regency, Bangka Belitung Islands Province. Modern Islamic Boarding School Uwais Al-Qarni is here by instilling noble character and adhering to the teachings of Islam that are rahmatan lilalamin which reflects a tolerant, moderate, humble attitude, and in accordance with the noble culture of the Indonesian nation through education and Islamic da'wah, exemplary and community empowerment within the framework of The Unitary State of the Republic of Indonesia. Forming a moderate religious understanding and love for the homeland. Increase human resources in order to meet educational needs that encourage the creation of religious harmony and benefit the social welfare of the community. The Islamic values ​​of rahmatan lilalamin should be based on Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Bhinneka Tunggal Ika.